The Relationship Between Personality Types, Learning Styles and Problem Solving Approach of Technical and Vocational Education Students - Othman, Widad; Sumarni, Rio; Lee, Ming Foong (Universiti Putra Malaysia Press, 2007)
Personality types and learning styles play an important role in higher education. They represent different individual preferences and strengths in learning; and can be a stimulus for developing new ways of learning. Engineering Drawing is one of the subjects for training students to become experts in graphic communication. Students who learn Engineering Drawing acquire a strong foundation, which enable them to work in the field of engineering or to continue their studies. This research reported here focused on the relationship between personality types, learning styles and problem solving at visualization level among final year Technical and Vocational Education (TVE) students in University Technology Malaysia. The Eysenck Personality Questionnaire (EPQ), Kolb Learning Styles Inventory (LSI) and Hatta Effective Problem Solving Approach were used to measure the different personality types, learning styles and effective problem solving for engineering drawing respectively. A total of 33 respondents from three different areas of TVE specifically Civil, Electrical and Mechanical Engineering were randomly selected as samples. The results showed that phlegmatic personality type students tend to have divergent learning style, followed by convergent and accommodator learning styles. The results also implied that sanguine personality type students tend to possess divergent learning style, followed by convergent learning style, while the melancholic personality type students preferred divergent and convergent learning styles. The method used by students to solve engineering drawing problems is a combination of imagination and sketching. However there is no difference amongst students with different personalities and learning styles in solving engineering drawing problems.